Sociocultural and demographic factors that influence academic performance: The pre-university case of the Universidad Politécnica Estatal del Carchi - Eduardo Javier Pozo Burgos; Marco Rubén Burbano Pulles; Jack Iván Vidal Chica; Gabriela Elizabeth Revelo Salgado (OmniaScience, 2022)
The pre-university course established at the Universidad Politécnica Estatal del Carchi (UPEC) after the disappearance of the Sistema Nacional de Nivelación y Admisión (National Equalization and Admissions System, known by its Spanish acronym as the SNNA) posed new challenges for the organizational and academic structure of this university. To start with, the challenge began with the adaptation of a curricular structure according to the educational needs of the nine undergraduate degrees offered at the university. It was followed by the implementation of the program, and finally its evaluation. The present research was designed and carried out as part of the latter goal. Its main objective was to determine the sociocultural and demographic factors that influence the academic performance of the students in the course. For the purposes of this investigation, from a methodological perspective, academic performance was associated with the number of subjects passed by the student. Using multivariate dependency techniques, a logistic regression was performed, which determined the degree of incidence of sociocultural and demographics factors on academic success. After applying the model, the results indicated that the demographic factors in this case do not influence academic success, while variables such as the educational level of the student's parents, the student's grade on university entrance exams and work status are significant when it comes to establishing a cause and effect relationship in this case study.